Fabrication of sodium potassium niobate ceramics by two step sintering assisted molten salts synthesis - Narumon Lartcumfu (2018)
Potassium sodium niobate (KNN) powders were synthesized by a molten salt synthesis. The pure phase KNN was achieved for a calcination temperature of 500 °C which is lower than the conventional technique by 400°C. The KNN ceramics were then fabricated by a two steps sintering technique. Effects of dwell time at T 2 on the properties of the ceramics were investigated. Although there was unchanged in microstructure, the dielectric results indicate that a longer dwell time produced a higher value of peak dielectric constant. However, the 8 h sample exhibited the densest ceramic and showed a better ferroelectric performance. © 2013 Copyright Taylor and Francis Group, LLC.